Transcriptional Profiles of Long Non-coding RNA and mRNA in Sheep Mammary Gland During Lactation Period - Chen, Weihao; Lv, Xiaoyang; Wang, Yue; Zhang, Xinjun; Wang, Shanhe; Hussain, Zahid; Chen, Ling; Su, Rui; Sun, Wei (Frontiers in Genetics, 2020)
Sheep milk and related products have been growing in popularity around the world in recent years. However, the sheep milk industry is limited by low sheep milk yield, and the molecular regulators of sheep lactation remain largely unknown. To investigate the transcriptomic basis of sheep lactation, RNA-sequencing was used to explore the expression profiles of lncRNA and mRNA of the mammary gland in Hu sheep at three key time points during the lactation stage: five days before the expected date of parturition (perinatal period, PP), six days after parturition (early lactation, EL), and 25 days after parturition (peak lactation, PL). A total of 1,111, 688, and 54 differentially expressed (DE) lncRNAs as well as 1,360, 660, and 17 DE mRNAs were detected in the EL vs. PP, PL vs. PP, and PL vs. EL comparisons, respectively. Several key mRNAs (e.g. CSN1S1, CSN1S2, PAEP, CSN2, CSN3, and COL3A1) and lncRNAs (e.g. LNC_018483, LNC_005678, LNC_012936, and LNC_004856) were identified. Functional enrichment analysis revealed that several DE mRNAs and target genes of DE lncRNAs were involved in lactation-related pathways, such as MAPK, PPAR, and ECM-receptor interaction. This study enhances our understanding of how transcriptomic profiles change during the lactation period and promises to aid future studies examining sheep lactation.